O ensino de geografia nos anos iniciais do ensino fundamental em uma escola rural de Miracema e a formação do pedagogo - Silva, Helisnay Pinheiro da (Universidade Federal do Tocantins, 2022)
This monograph is the result of the debates of my training in the Pedagogy Course-UFT/Campus de Miracema, in the context of the set of teaching, research and extension activities in which I participated, but mainly of the reflections and practices articulated with the internship and the practice of teaching, with the activities of PIBID, in the activities of Prodocência, as well as the debates arising from my participation in the EDURURAL Research Group. Its objective was to investigate the Pedagogy Course and the processes of my formation in this course, seeking to understand how the teaching of Geography is developed in the early years at the Boanerges Moreira de Paula Municipal School, located in the Brejinho Settlement, in the municipality of Miracema do Tocantins. It is a qualitative research, with a bibliographic basis and based on a field research with data collected from teachers of the researched school and students from the Pedagogy Course at UFT/Campus de Miracema. These data were collected from a semi-structured interview and analysis of the Political Pedagogical Project of the School and articulated with the studied literature. Working with geographic content in the early years is a challenge for pedagogues. It was noticed that there is a lot of individual effort from teachers to make possible a training process that articulates the experiences and knowledge of children and their families with the world of school. However, we understand that there are issues that are not possible because the school was not and is not designed for this to happen.